10 High spontaneous ductal closure even at the extreme of prematurity. (29th October 2021) - de Carvalho Nunes, Gabriela; Wutthigate, Punnanee; Simoneau, Jessica; Beltempo, Marc; Sant'Anna, Guilherme; Altit, Gabriel
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Extremely preterm newborns are at risk of prolonged patency of the ductus arteriosus (PDA). Current literature has failed to indicate improvement in outcomes after exposure to strategies promoting ductal closure. As such, our center abandoned these practices in 2013. Objectives: Describe the spontaneous PDA closure in premature infants, including those infants born at the extreme of gestational age (< 26 weeks). Design/Methods: Retrospective study of newborns < 29 weeks, admitted within 24 hours after birth between 2015 and 2019 and without genetic or congenital anomalies. Newborns who were last known to be alive, with an available echocardiography, and who were not exposed to any intervention to accelerate PDA closure were included. Images were reviewed by experts blinded to the outcomes. Results: 296 infants were analyzed. 37 (12%) did not survive their hospitalization, and 16 were exposed to interventions to accelerate ductal closure at some point during their lifetime (4 ligations, 4 catheter-closure, 5 ibuprofen and 3 acetaminophen). Out of the 243 remaining newborns, 214 had at least one echocardiography to ascertain ductal patency or closure (100% of those <26 weeks). The average gestational age was 26.3±1.5 weeks, with 84 (39%) being <26 weeks. PDA closed spontaneously in 194 (91%), with 60 having closure ascertainment after discharge (average age at closure ascertainment of 36.4 [IQR: 34.4 – 40.1] weeks). Of the 84 <26 weeks, 76 (90%) had confirmation of ductal closure. The 20 infants with an open PDA at the last evaluation were followed in an outpatient setting and considered small/restrictive. In our cohort, 92/243 (38%) were exposed to post-natal steroids. In the <26 weeks group, 74% were exposed to steroids, at a cumulative dose of 1.64 [0.89 – 2.44] mg/kg. BPD was found in 57% of the overall cohort and in 79% of <26 weeks. Conclusion: The majority of newborns < 29 weeks, and even those at the extreme of gestational age (< 26 weeks) spontaneously closed their PDA before term-corrected age. While BPD rate was similar to previous cohorts, post-natal steroids use was high.